PERAN PEMULUNG DALAM SISTEM PENGELOLAAN SAMPAH DI TEMPAT PENAMPUNGAN SEMENTARA (TPS) SLEMAN YOGYAKARTA - andar dhini (Industry Xplore, 2022)
Every year, Indonesia faces the population growth that impacted to public growth consumption and it is conduces the amount of litters. The scavenger indicated as an important role to detract the volume of litter from the initial sources. The research aims to indicate the scavengers performances who are responsible to reduce and sort the litters. The temporary disposal garbage known as TPS is one of the initial sources take place. TPS Condongcatur, TPS Tridadi and TPS Tambakboyo have the highest volume litters in Sleman, Yogyakarta. These three places used as the samples to this research. The method was adapted through SNI 19-3964-1994 followed by interview sections and questionnaires. This study took 8 days sequential and the total scavengers has interviewed was 17 people for all the places. The outcome of this study shown that the average of garbage volume in TPS Condongcatur was 18,86m³/days. TPS Tridadi has 16,31m³/days and TPS Tambakboyo 25,66m³/days for the average of garbage volumes. Whilst, The garbage percentage volume that sorted by scavengers in TPS Condongcatur was 5,4% meanwhile in TPS Tridadi was 8,23% and Tambakboyo was 22,1%. The average litter residues was 8,44% for TPS Condongcatur, TPS Tridadi was 8,05% and TPS Tambakboyo was 7,94%. The residuals garbage was opium by trucks while picked the garbage up.